Design and Discovery of 6‑[(3S,4S)‑4-Methyl-1-(pyrimidin-2-ylmethyl)pyrrolidin-3-yl]-1-(tetrahydro‑2H‑pyran-4-yl)-1,5-dihydro‑4H‑pyrazolo[3,4‑d]pyrimidin-4-one (PF-04447943), a Selective Brain Penetrant PDE9A Inhibitor for the Treatment of Cognitive Disorders - Verhoest, Patrick R; Fonseca, Kari R; Hou, Xinjun; Proulx-LaFrance, Caroline; Corman, Michael; Helal, Christopher J; Claffey, Michelle M; Tuttle, Jamison B; Coffman, Karen J; Liu, Shenpinq; Nelson, Frederick; Kleiman, Robin J; et al. (Journal of medicinal chemistry, 2012)
6-[(3S,4S)-4-Methyl-1-(pyrimidin-2-ylmethyl)pyrrolidin-3-yl]-1-(tetrahydro-2H-pyran-4-yl)-1,5-dihydro-4H-pyrazolo[3,4-d]pyrimidin-4-one (PF-04447943) is a novel PDE9A inhibitor identified using parallel synthetic chemistry and structure-based drug design (SBDD) and has advanced into clinical trials. Selectivity for PDE9A over other PDE family members was achieved by targeting key residue differences between the PDE9A and PDE1C catalytic site. The physicochemical properties of the series were optimized to provide excellent in vitro and in vivo pharmacokinetics properties in multiple species including humans. It has been reported to elevate central cGMP levels in the brain and CSF of rodents. In addition, it exhibits procognitive activity in several rodent models and synaptic stabilization in an amyloid precursor protein (APP) transgenic mouse model. Recent disclosures from clinical trials confirm that it is well tolerated in humans and elevates cGMP in cerebral spinal fluid of healthy volunteers, confirming that it is a quality pharmacological tool for testing clinical hypotheses in disease states associated with impairment of cGMP signaling or cognition.